2019
DOI: 10.2217/bmm-2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Significance of Octamer-Binding Transcription Factor 4 in Patients with Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: Aim: The role of octamer-binding transcription factor 4 (Oct4) in gastric cancer (GC) progression is still under debate and reported results are inconsistent. Therefore, we conducted a meta-analysis to evaluate the clinicopathological and prognostic significance of Oct4 expression in patients with GC. Materials & methods: Relevant articles were retrieved from a diverse number of databases, and meta-analysis was completed using STATA software 12.0. Results: Total of 21 studies were included in this analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…As for cervical cancer, Liu et al [297] found that the aberrant activity of HDAC1 in C-33A cells significantly increases the expression of octamer-binding embryonic transcription factor 4 (Oct4), a prognostic biomarker of various types of malignancies that plays a critical role in maintaining the pluripotency and self-renewal of embryonic stem cells [308][309][310][311]. The contribution of histone deacetylase 1 to the maintenance of stem properties in transformed cells was also shown in a recent study by Yokoi et al [312], where an abnormal HDAC 1 expression profile in the ME180 and CaSki cell lines led to the activation of the Oct4, Nanog, and SOX2 genes that exhibit oncogenic function.…”
Section: Changes In the Intensity Of Histone Acetylation During Oncog...mentioning
confidence: 99%
“…As for cervical cancer, Liu et al [297] found that the aberrant activity of HDAC1 in C-33A cells significantly increases the expression of octamer-binding embryonic transcription factor 4 (Oct4), a prognostic biomarker of various types of malignancies that plays a critical role in maintaining the pluripotency and self-renewal of embryonic stem cells [308][309][310][311]. The contribution of histone deacetylase 1 to the maintenance of stem properties in transformed cells was also shown in a recent study by Yokoi et al [312], where an abnormal HDAC 1 expression profile in the ME180 and CaSki cell lines led to the activation of the Oct4, Nanog, and SOX2 genes that exhibit oncogenic function.…”
Section: Changes In the Intensity Of Histone Acetylation During Oncog...mentioning
confidence: 99%